Examining classroom learning behaviors academic and athletic motivation in collegiate athletes - Kayleigh Hart; Leilani Madrigal; Alison Ede; Jana Fogaca (University of Kansas Libraries, 2024)
College student-athletes balance the demands of both sport and school in the context of higher education; high levels of motivation are necessary for success in both spaces. Studies have evaluated learning styles and academic motivational outcomes in college student athletes but there is a need to explore how motivation impacts both academic and athletic success. The present study examined the relationship academic, student athletic, and career athletic motivation had with learning styles and major (STEM vs. non-STEM) using Self-Determination Theory as the theoretical lens. College Division I, II, III, and Club college athletes took the Grasha-Reichmann Student Learning Style Scale and Student Athletes Motivation toward Sports and Academics Questionnaire. Learning styles were grouped into intrinsic (independent, participant, and collaborative) and extrinsic (dependent, avoidant, and competitive) styles. There were positive relationships between intrinsic learning style and both student athletic (r(147) = .19, p = .02) and academic (r(147) = .30, p < .001) motivation. Extrinsic learning style was positively correlated with career athletic (r(147) = .27, p = .001) and student athletic (r(147) = .16, p < .05) motivation but negatively corelated with academic motivation (r(147) = -.17, p = .03). Athletes in STEM majors (M = 3.88, SD = 0.36) had significantly higher academic motivation than non-STEM majors (M = 3.66, SD = 0.40), t(182) = 3.85, p < .001. Athletes in non-STEM majors (M = 4.00, SD = 0.88) had significantly higher career athletic motivation than STEM majors (M = 3.56, SD = 0.91), t(182) = -3.29, p = .001. Findings suggest being more independent, participant, and collaborative in class is related to motivation both in school and in student athletic endeavors. Athletes pursuing a STEM major may show higher academic motivation than athletes pursuing non-STEM majors. Encouraging student-athlete learning autonomy via education/intervention could improve intrinsic motivation in sport and classes, though further exploration of these factors is necessary to fully understand their relationship in college student-athletes.